Evaluation of analgesic, Antipyretic and anti-inflammatory activities of the ethanol and dichloromenthane extract from scaphium lychnophorum fruit in experiment animals - Pancharee Surapanthanakorn (Prince of Songkla University, 2011)
Thesis (M.Sc., Pharmacology)--Prince of Songkla University, 2010